2020
DOI: 10.1186/s40463-020-00424-7
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-generating otolaryngology procedures and the need for enhanced PPE during the COVID-19 pandemic: a literature review

Abstract: Background: Adequate personal protective equipment is needed to reduce the rate of transmission of COVID-19 to health care workers. Otolaryngology groups are recommending a higher level of personal protective equipment for aerosol-generating procedures than public health agencies. The objective of the review was to provide evidence that a.) demonstrates which otolaryngology procedures are aerosol-generating, and that b.) clarifies whether the higher level of PPE advocated by otolaryngology groups is justified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
224
1
16

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(248 citation statements)
references
References 65 publications
(77 reference statements)
2
224
1
16
Order By: Relevance
“…Our preliminary experience and early experience from other Italian 26 38 and Chinese39 studies supports the safety of tracheostomy if appropriate protocols are strictly followed. After one month from the last tracheostomy we performed no one of our team developed symptoms of COVID-19.…”
Section: Discussionsupporting
confidence: 53%
“…Our preliminary experience and early experience from other Italian 26 38 and Chinese39 studies supports the safety of tracheostomy if appropriate protocols are strictly followed. After one month from the last tracheostomy we performed no one of our team developed symptoms of COVID-19.…”
Section: Discussionsupporting
confidence: 53%
“…33 As per a recent paper by Guo et al, 34 the transmission distance of SARS-CoV-2 aerosol might reach 4 m. The same study also found that 'SARS-CoV-2 was widely distributed in the air and on object surfaces in both the intensive care unit and general ward, implying a potentially high infection risk for medical staff and other close contacts'. 33,34 Functional endoscopic sinus surgery, and anterior skull base surgery more specifically, typically entail manoeuvres and instrumentation employed in or through high viral load areas, which can cause aerosolisation of viral particles in the mucosa. 4,20 The use of drills, microdebriders, electrocautery, advanced energy devices and suctioning further promotes aerosol formation and the possible shedding of infectious microdroplets throughout the operating theatre.…”
Section: Discussionmentioning
confidence: 60%
“…This is especially important given the concerns regarding leaks in filtering facepiece code 2 masks and N95 mask respirators (used in many countries) during long procedures. 33 Adoption of the microscope drape technique could also result in faster operating theatre cleaning and turnover associated with the significantly reduced air particle or aerosol spread in the operating theatre by the end of the AGP, and potentially allow more liberal use of powered instruments during endonasal surgery. Furthermore, it could be argued that the use of an air particle counter in the operating theatre would be valuable for alerting staff to a potential significant aerosol leak through the drape, and assisting in decision making with respect to doffing PPE and operating theatre cleaning and turnover.…”
Section: Discussionmentioning
confidence: 99%
“…A key focus at this point in the patient pathway is ensuring staff safety and the efficient use of resources. 14,15 This relates to the both the provision of theatre space in addition to the use of full personal protective equipment (PPE). Theatre list capacity has reduced due to the increased time required to intubate and extubate the patient.…”
Section: Intraoperative Carementioning
confidence: 99%